2009
DOI: 10.1111/j.1365-2656.2009.01604.x
|View full text |Cite
|
Sign up to set email alerts
|

Identifying predators clarifies predictors of nest success in a temperate passerine

Abstract: Summary1. Nest predation negatively affects most avian populations. Studies of nest predation usually group all nest failures when attempting to determine temporal and parental activities, habitat or landscape predictors of success. Often these studies find few significant predictors and interpret patterns as essentially random. 2. Relatively little is known about the importance of individual predator species or groups on observed patterns of nest success, and how the ecology of these predators may influence p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
115
1
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 126 publications
(130 citation statements)
references
References 68 publications
13
115
1
1
Order By: Relevance
“…, snakes are more likely to depredate nests during the nestling phase(Benson et al, 2010;Stake et al, 2005), an association we found for Cerulean Warblers.Fig. 5.…”
supporting
confidence: 66%
“…, snakes are more likely to depredate nests during the nestling phase(Benson et al, 2010;Stake et al, 2005), an association we found for Cerulean Warblers.Fig. 5.…”
supporting
confidence: 66%
“…Alternatively, landscape structure and nest location may mediate predation risk through alteration of predator searching behavior and/or the influence of habitat structure in impeding predator searches (24,30). Indeed, there is supporting evidence from temperate regions that predation pressure can vary among major nest predator types as a function of area (30,31) and distance to edge (31)(32)(33). There is also evidence from temperate regions that habitat structure of nest sites can mediate predation risk via changes in predator searching behavior (29).…”
Section: Discussionmentioning
confidence: 99%
“…, Benson et al 2010, Bolton et al 2007, Brown et al 1998, Buler and Hamilton 2000, Carter et al 2007, Coates et al 2010, Conner et al 2010, Farnsworth and Simons 2000, Franca et al 2009, Franzreb 2007, Granfors et al 2001, Grant et al 2006, Herranz et al 2002, King and DeGraaf 2006, Liebezeit and George 2003, Lusk et al 2006, Major and Gowing 1994. Marzluff et al 2007, McKinnon and Bety 2009, Moore and Reid 2009, Morgan et al 2006, Morrison and Bolger 2002, Perkins et al 2005, Peterson et al 2004, Pietz and Granfors 2000.…”
Section: Discussionmentioning
confidence: 99%